Identification and functional analysis of ovarian lncRNAs during different egg laying periods in Taihe Black-Bone Chickens - Huang, Yunyan; Li, Shibao; Tan, Yuting; Xu, Chunhui; Huang, Xuan; Yin, Zhaozheng (Frontiers in Physiology, 2024)
Long non-coding RNA (lncRNA) refers to a category of non-coding RNA molecules exceeding 200 nucleotides in length, which exerts a regulatory role in the context of ovarian development. There is a paucity of research examining the involvement of lncRNA in the regulation of ovary development in Taihe Black-Bone Chickens. In order to further investigate the laying regulation mechanisms of Taihe Black-Bone Chickens at different periods, this study randomly selected ovarian tissues from 12 chickens for RNA-seq. 4 chickens were selected for each period, including the early laying period (102 days, Pre), the peak laying period (203 days, Peak), and the late laying period (394 days, Late).Based on our previous study of mRNA expression profiles in the same ovarian tissue, we identified three differentially expressed lncRNAs (DE lncRNAs) at different periods and searched for their cisand trans-target genes to draw a lncRNA-mRNA network. In three groups of ovarian tissues, we identified 136 DE lncRNAs, with 8 showing the early laying period specific expression, 10 showing the peak laying period specific expression, and 4 showing the late laying period specific expression.The lncRNA-mRNA network revealed 16 pairs of lncRNA-target genes associated with 7 DE lncRNAs, and these 14 target genes were involved in the regulation of reproductive traits.Furthermore, these reproductive-related target genes were primarily associated with signaling pathways related to follicles and ovary development in Taihe Black-Bone Chickens , including cytokine-cytokine receptor interaction, TGF-beta signaling pathway, tyrosine metabolism, ECMreceptor interaction, focal adhesion, neuroactive ligand-receptor interaction, cell adhesion molecules (CAMs), This study offers valuable insights for a comprehensive understanding of the influence of lncRNAs on poultry reproductive traits.